เฮือน 3 น้ำ 4 ที่มีผลต่อการดำเนินชีวิตของชุมชนตำบลยางท่าแจ้ง อำเภอโกสุมพิสัย จังหวัดมหาสารคาม - Soontharo (Namo), Phra Suprom; Phrakhru Sudhikhambhirayan; lhanwong, Adul (Journal of Modern Learning Development, 2022)
This thesis The objectives were: 1) to study Huan 3 Nam 4 in Isan literature; 2) To study Huan 3 Nam 4 that influenced the way of life of the Yang Tha Chaeng sub-district community. Kosoom Phisai District Maha Sarakham Province and 3) to study Huan 3 Nam 4 activities that affect the lifestyle of Yang Tha Chaeng sub-district community. Kosum Phisai District Maha Sarakham Province This is a qualitative research by analyzing descriptive data. The results showed that Huan 3 Nam 4 in Isan literature by using intervening principles to point out the guidelines and the consequences of non-compliance with Buddhist principles concerning virtues appearing in the literature have the virtues of showing respect for each other Asceticism, sacrifice, the ethical part that appears there is gratitude. love, compassion, morals Principles that promote the values ​​and beauty of women as tools for developing a woman's conduct to be more beautiful with Huan 3 Nam 4 are 1) external beauty is physical beauty that can be seen as concrete, and 2) internal beauty is the Beauty that focuses on the mental state of the person. Having the virtues of the mind, tolerance, patience, soraccha, easiness, and the four sagnaha-vatthana, which consist of alms, piyavaca, atthachariya, and samanatta. Benjakalayani and Huan 3 waters 4 consist of the "three houses" i.e. the body, the hair and the living or sleeping houses. The "four waters" consist of the heart, the water, the hands, and the gourd or drinking water. The water used for Huan 3 Nam 4 affecting the life of the Yang Tha Chaeng sub-district community Kosum Phisai District Maha Sarakham Province Women's beauty values ​​are valuable and important elements. is good manners and practices or good character and good manners including the value of self-improvement to have morals in mind Good self-control, good modesty, good self-doubt, family and community. "House of Three Nam Four" If any woman has all these elements, it will be regarded as a good woman. be a good wife and have the opportunity to have a good spouse In addition, today's parents are increasingly obliged to work outside the home to earn money to support the family in the current high cost of living. Parents therefore have less time to inculcate the habits of their children on this issue. Such values ​​have changed over time. In addition to the influence of foreign cultures that permeate the era of globalization.